A business model perspective on knowledge-intensive services in the software industry. (20th April 2007) - Rajala, Risto; Westerlund, Mika
Specialisation in core competencies as a response to intense competition from entrepreneur-driven SMEs in technology and knowledge-intensive industries such as the software industry demands network-focused business behaviour and the utilisation of resources beyond company boundaries. In recent years, the outsourcing of Knowledge-Intensive Services (KIS), for example, has emerged as a phenomenon in technology-oriented enterprises and has attracted increasing attention in the literature on business and entrepreneurship. However, KIS have not been sufficiently analysed in connection with different types of business models. Drawing on theories of inter-organisational exchange, including the industrial network approach and Transaction Cost Economics (TCE), we analyse key KIS in four different types of business models of software companies. According to our findings, the role and type of KIS vary systematically by business-model type.